Ionization by keV election precipitation in the auroral zone - Kaya, Nobuyuki; Matsumoto, Haruya (1982)
P(論文) The electron fluxes precipitating into the aurora zone were observed by the electron spectrometers (ESM) onboard the Japanese Antarctic sounding rockets S-310JA-5 and -6 at Syowa Station in 1978. The ESM measured successfully the electron fluxes in the energy range of 1 to 10keV at small and near 90° pitch angles. The detailed description of the ESM instrument and the results of the observations were presented elsewhere (KAYA et al., 1981). The density of secondary electrons ionized by the precipitating electrons was estimated and compared with the data obtained by the impedance probe onboard the same rockets. The method of the calculation was based on KAMIYAMA (1966). The electron densities estimated by the calculation are 5 times more on the average than those measured by the impedance probe. However, there is a close resemblance in the fine structures of the altitude profiles of the electron density. departmental bulletin paper